PENGARUH KEPERCAYAAN DAN E-WOM TERHADAP NIAT PEMBELIAN ONLINE SERTA PERAN DEMOGRAFI SEBAGAI PEMODERASI PEMBELIAN ONLINE - ARISTANA, I DEWA GEDE (Universitas Mahasaraswati K. Mataram, 2023)
The Indonesian E-Commerce market, especially in the retail industry, is undergoing a phase of development, but behind the rapid growth of E-Commerce there are contradictory business issues related to online buying behavior. When internet usage is increasing in online shopping activities, a large number of prospective consumers actually decide to cancel at the final stage of completing online transactions, namely at the payment stage. The increase in the value of E-Commerce transactions was not followed by an increase in the ratio of online transaction settlement. The purpose of this research is to explain the effect of trust and Electronic Word of Mouth on online purchase intentions and online purchases, the mediating role of online purchase intentions, and the demographic moderation role on the effect of online purchase intentions on online purchases. Theories used as references are Theory of Planned Behavior (TPB) and Social cognitive theory. Respondents in this study were people of Denpasar City who had purchased fashion products online, in the past one month with a minimum age of 17 years, and had at least 1 purchase. Data analysis was performed using PLS (partial least square). The results of this study indicate that trust has a positive but not significant effect on online purchases and on online purchase intentions has a positive and significant effect, E-WOM has a positive and significant influence on the intention of online purchase and online purchase, intention to purchase online has a positive effect and significant to online purchases. Online purchase intention mediates perfectly the effect of trust in online purchases, while the partial influence is shown by online purchase intention in mediating the effect of E-WOM on online purchases, and demographics are not able to moderate the influence of online purchase intentions on online purchases.